Direct Healthcare Costs by Level of Adherence of a Real-World Population of Statin Users in Italy - Degli Esposti L; Veronesi C; Ancona DD; Andretta M; Bartolini F; Drei A; Lupi A; Palcic S; Re D; Rizzi FV; Giacomini E; Perrone V (Dove Medical Press, 2022)
Luca Degli Esposti,1 Chiara Veronesi,1 Domenica Daniela Ancona,2 Margherita Andretta,3 Fausto Bartolini,4 Alberto Drei,5 Alessandro Lupi,6 Stefano Palcic,7 Davide Re,8 Francesca Vittoria Rizzi,2 Elisa Giacomini,1 Valentina Perrone1 1CliCon S.r.l. Health, Economics & Outcomes Research, Bologna, Italy; 2Dipartimento Farmaceutico, ASL BAT, Trani, Italy; 3UOC Assistenza Farmaceutica Territoriale, Azienda ULSS 8 Berica, Vicenza, Italy; 4Dipartimento Farmaceutico, Umbria 2, Terni, 05100, Italy; 5Deloitte, Milano, Italy; 6Cardiology Unit, ASL VCO, Omegna, Italy; 7Farmaceutica Territoriale, Azienda Sanitaria Universitaria Integrata Giuliano-Isontina, Trieste, Italy; 8UOC Assistenza Farmaceutica Territoriale, ASL Teramo, Teramo, ItalyCorrespondence: Valentina Perrone, Clicon Srl, Health, Economics and Outcomes Research, Via Murri 9, Bologna, 40137, Italy, Tel +39 544 38393, Fax +39 544 212699, Email valentina.perrone@Clicon.itPurpose: This real-world study investigates the direct healthcare costs from the perspective of the Italian Healthcare National Service of experienced statin users according to their level of adherence to therapy and to their cardiovascular (CV) profile in Italian settings of outpatients clinical practice.Patients and Methods: A retrospective observational analysis was performed based on administrative databases covering approximately 6 million health-assisted individuals. Adult patients with statins prescription between January 2014 and December 2016 were screened, and first prescription within this period was the index date. Follow-up lasted 1 year after index date. Only patients receiving statins prior index date (experienced statin users) were included and distributed in clusters based on their CV profile. Adherence was calculated during follow-up as proportion of days covered (PDC) and classified in low adherence (PDC< 40%), partial adherence (PDC=40- 79%) and adherence (PDC≥ 80%). Mean direct healthcare costs of drugs, hospitalizations, and outpatient services were evaluated during follow-up.Results: A total of 436,623 experienced statin users were included and distributed as follows: 5.5% in the previous CV events, 22.6% in diabetes, 55.7% in CV treatments and 16.2% in the no comorbidity cluster. Total mean annual cost/patient decreased from low adherent to adherent patients from € 4826 to € 3497 in previous CV events, from € 2815 to € 2360 in diabetes cluster, from € 2077 to € 1863 for patients with CV treatments. Same trend was reported for the cost item related to hospitalizations, which was the major determinant of the total costs. In previous CV event cluster, adherence was associated to a saving of € 879 on total costs.Conclusion: The study highlighted a decrease in overall mean costs as adherence levels increase, particularly for patients with previous CV events, showing how improving adherence could be associated to cost savings and suggesting suited strategy based on CV profile should be undertaken for adherence optimization.Keywords: direct costs, lipid-lowering drugs, medication adherence, real-life